1997
DOI: 10.1055/s-2007-972601
|View full text |Cite
|
Sign up to set email alerts
|

Blood Glutathione Status Following Distance Running

Abstract: In 12 moderately trained subjects reduced glutathione (GSH) and oxidized glutathione (GSSG) as well as thiobarbituric acid reactive substances (TBARS) were measured in the blood before and during the first two hours and first two days after a 2.5-h run. The participants covered between 19 and 26 km (20.8 +/- 2.5 km, mean +/- SD). The running speed was between 53 and 82% of the speed at which blood lactate concentration reached 4 mmol/L lactate (67.9 +/- 8.2%, mean +/- SD) assessed during a previously performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 6 publications
1
18
1
1
Order By: Relevance
“…Together, with the present findings, these data suggest that a high-intensity interval session may more readily deplete vitamin E when compared with a 30 km time trial, to protect against increased oxidative stress. Vitamin E is an important component of the lipid membrane and offers protection against lipid peroxidation (Duthie et al 1990;Dufaux et al 1997;Marzatico et al 1997;Groussard et al 2003). The decrease in plasma vitamin E following the interval session may have contributed to the increased susceptibility of lipids to peroxidation following the same trial, as indicated by the increase in plasma MDA concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Together, with the present findings, these data suggest that a high-intensity interval session may more readily deplete vitamin E when compared with a 30 km time trial, to protect against increased oxidative stress. Vitamin E is an important component of the lipid membrane and offers protection against lipid peroxidation (Duthie et al 1990;Dufaux et al 1997;Marzatico et al 1997;Groussard et al 2003). The decrease in plasma vitamin E following the interval session may have contributed to the increased susceptibility of lipids to peroxidation following the same trial, as indicated by the increase in plasma MDA concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation has been evaluated by measuring malondialdehyde (MDA) concentrations using the thiobarbituric acid reactive substances (TBARS) assay, but this method has often been criticized for its indirect reaction with LPO and lack of speci®city for free MDA formed in vivo (Kanazawa et al 1989;Dufaux et al 1996). Therefore, we used the HMB test to measure LPO, which has been shown to be more speci®c for LPO than the TBARS test (Kanazawa et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been hypothesized that exhausting exercise can cause lipid peroxidation due to the marked increase of oxygen uptake and production of reactive oxygen species by activated phagocytes (Suzuki et al 1996a(Suzuki et al , b, 1999. Although the body is well equipped with an antioxidant defence system to prevent the potentially harmful eects of these free radicals, lipid peroxidation can occur when these radicals overwhelm the antioxidative capacity, and free radical-mediated muscle damage after exercise has been suggested (Dufaux et al 1996;Suzuki et al 1996aSuzuki et al , 1999. We therefore measured plasma indices of NO production and lipid peroxidation together with muscle damage markers following exhausting exercise.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, indirect parameters were determined by measuring side products of lipidperoxidation such as determination of pentane (Dillard et al 1978) and ethane in exhaled air, and of malondialdehyde and isoprostane (Mastaloudis et al 2001) in the blood or of glutathione and oxidized glutathione (Dufaux et al 1997;Duthie et al 1990) in erythrocytes.…”
Section: Introductionmentioning
confidence: 99%